Iron chelation therapy with deferiprone improves oxidative status and red blood cell quality and reduces redox-active iron in β-thalassemia/hemoglobin E patients - Noppawan Phumala Morales (2022)
The oxidative status of twenty-three β-thalassemia/hemoglobin E patients was evaluated after administration of 75 mg/kg deferiprone (GPO-L-ONE®) divided into 3 doses daily for 12 months. Serum ferritin was significantly decreased; the median value at the initial and final assessments was 2842 and 1719 ng/mL, respectively. Progressive improvement with significant changes in antioxidant enzyme activity, including plasma paraoxonase (PON) and platelet-activating factor acetylhydrolase (PAF-AH), and in antioxidant enzymes in red blood cells (glutathione peroxidase (GPx), catalase and superoxide dismutase (SOD)) were observed at 3–6 months of treatment. The levels of total GSH in red blood cells were significantly increased at the end of the study. Improved red blood cell membrane integrity was also demonstrated using the EPR spin labeling technique. Membrane fluidity at the surface and hydrophobic regions of the red blood cell membrane was significantly changed after 12 months of treatment. In addition, a significant increase in hemoglobin content was observed (6.6 ± 0.7 and 7.5 ± 1.3 g/dL at the initial assessment and at 6 months, respectively). Correlations were observed between hemoglobin content, membrane fluidity and antioxidant enzymes in red blood cells. The antioxidant activity of deferiprone may partly be explained by progressive reduction of redox active iron that catalyzes free radical reactions, as demonstrated by the EPR spin trapping technique. In conclusion, iron chelation therapy with deferiprone notably improved the oxidative status in thalassemia, consequently reducing the risk of oxidative-related complications. Furthermore, the improvement in red blood cell quality may improve the anemia situation in patients.